Effect of the Flunixin Meglumine on Pregnancy Rates in an Equine Embryo Transfer Program - Okada, Carolina Tiemi Cardoso [UNESP]; Segabinazzi, Lorenzo Garrido [UNESP]; Crespilho, André Maciel; Dell'Aqua, José Antônio [UNESP]; Alvarenga, Marco Antonio [UNESP] (Elsevier, 2018)
During the equine embryo transfer (ET), manipulation of the recipients cervix can stimulate the release of prostaglandin F2α by the uterine environment. Nonsteroidal anti-inflammatory drugs such as flunixin meglumine (FM) are frequently used in order to prevent a potential luteolysis. However, despite the reduction of inflammatory reaction and release of prostaglandins, the benefits of FM in pregnancy rates (PRs) of mares submitted to ET are not conclusive, and there is no information about the early pregnancy loss (EPL) rate after FM injection. The objective of this study was to evaluate the effect of FM in the PR and EPL in embryo-recipient mares. The data from 409 ET from a commercial breeding center were used, which 179 mares formed the control group (CG) and 230 recipients received the treatment of FM 1.1 mg/kg immediately after ET. There was no difference (P >.05) in PRs at 15 days (70.95% in the CG and 75.22% in treated mares) and 60 days (65.92% in CG and 65.22% in FM treated mares). However, there was a trend in the increase of early the pregnancy loss rate in mares that received FM (P =.0852). From the results of the present experiment, FM does not improve the PR in embryo-recipient mares.
Keywords: Embryo transfer; Flunixin meglumine; Mare; Pregnancy rate